The keeping quality and palatability of mayonnaise and salad dressing made from coconut oil - San Pedro, Helen Torres 1940- (1961)
The study involves the preparation of three different consistencies of mayonnaise and salad dressing using coconut oil as an alternative to cottonseed oil, which is usually used for the manufacture of these emulsions. Furthermore, the study seeks to observe the physical and chemical changes that the created products undergo during storage, and lastly, to test the palatability and acceptability of these products.